2015
DOI: 10.1016/j.drugalcdep.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent ethanol exposure reduces presynaptic dopamine neurotransmission in the mouse nucleus accumbens

Abstract: BACKGROUND Increasing evidence suggests that chronic ethanol exposure decreases dopamine (DA) neurotransmission in the nucleus accumbens (NAc), contributing to a hypodopaminergic state during withdrawal. However, few studies have investigated adaptations in presynaptic DA terminals after chronic intermittent ethanol (CIE) exposure. In monkeys and rats, chronic ethanol exposure paradigms have been shown to increase DA uptake and D2 autoreceptor sensitivity. METHODS The current study examined the effects of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 65 publications
6
70
4
Order By: Relevance
“…The increased uptake of DA observed in the NAc core and shell of SI rats in the current study and in the NAc core in a previous report suggests that SI leads to augmented DAT levels in this brain region (Yorgason et al, 2015). Interestingly, other forms of chronic stress, such as repeated restraint stress, have also been shown to enhance DA uptake in the striatum (Copeland et al, 2005) and chronic ethanol exposure increases DA uptake in adult mouse, rat, and monkey models (Budygin et al, 2003;Karkhanis et al, 2015). An increase in DAT function would be expected to decrease overall extracellular DA levels.…”
Section: Adolescent Si Disrupts Da Transmission In the Nacmentioning
confidence: 64%
See 1 more Smart Citation
“…The increased uptake of DA observed in the NAc core and shell of SI rats in the current study and in the NAc core in a previous report suggests that SI leads to augmented DAT levels in this brain region (Yorgason et al, 2015). Interestingly, other forms of chronic stress, such as repeated restraint stress, have also been shown to enhance DA uptake in the striatum (Copeland et al, 2005) and chronic ethanol exposure increases DA uptake in adult mouse, rat, and monkey models (Budygin et al, 2003;Karkhanis et al, 2015). An increase in DAT function would be expected to decrease overall extracellular DA levels.…”
Section: Adolescent Si Disrupts Da Transmission In the Nacmentioning
confidence: 64%
“…Many studies have demonstrated that chronic stress, particularly during adolescence, results in a dysfunctional DA system (Broom and Yamamoto, 2005;Lucas et al, 2007;Karkhanis et al, 2015), which may result in a hypodopaminergic state. A hypodopaminergic state is classically characterized by reduced extracellular DA levels (tonic) but increased electrically stimulated DA release (phasic) and uptake rates (Mathews et al, 2009).…”
Section: Adolescent Si Disrupts Da Transmission In the Nacmentioning
confidence: 99%
“…Further, dysphoric states during withdrawal are mediated by changes in Acb neurotransmission, with alcohol-induced reductions in monoaminergic function theorized to contribute to the depressive effects of alcohol withdrawal. [23, 74, 75], Moreover, we know that a chronic history of binge drinking elevates indices of glutamatergic signaling within the Acb [15, 73]. Thus, we hypothesized at the outset of this study that a history of binge drinking would augment Acb cellular activity, particularly within the AchSh, and this increased activity would correlate with behavioral indices of negative affect.…”
Section: Discussionmentioning
confidence: 98%
“…Thus these differences may also be due to exposure length or strain; future studies will aim to systematically examine the hypothesis that these differences are due to sex. A second issue that should be addressed in future studies is differences in dopamine release changes induced by ethanol between these findings and rodent models, which have shown decreased dopamine release following chronic intermittent ethanol exposure via vapor inhalation (Karkhanis et al, 2015). These differences may be due to exposure length or route of administration; however, in all three studies (Siciliano et al, 2015a; Karkhanis et al, 2015; current study) dopamine uptake rate was increased by ethanol exposure, suggesting that alterations to the dopamine transporter may be a critical neurochemical adaptation induced by ethanol.…”
Section: Discussionmentioning
confidence: 99%